ANALISIS PENETAPAN MARGIN PADA PEMBIAYAAN MURABAHAH (STUDI KASUS PADA BPRS RAHMANIA DANA SEJAHTERA KABUPATEN BIREUEN) - Joely, Muhammad Ferdy; Ridwan, Ridwan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
Margin is the seller's rights agreed between the seller and the buyer. The profit margin is only found in the sale and purchase agreement. The percentage of profit obtained is an agreement between the seller and the buyer. So far, the BPRS in general still has difficulty in adjusting the determination of the margin, because if the BPRS sets the margin in accordance with applicable BI regulations, it will burden the BPRS because there are differences between customers, products and third party funds from the BPRS and Islamic commercial banks. This study aims to determine the determination of margins in murabaha financing at BPRS Rahmania Prosperous Bireuen Regency. This study uses descriptive qualitative methods, data collection techniques in research conducted interviews, observations, and documentation conducted directly with the SRB manager Rahmania Dana Sejahtera Bireuen Regency. This research resulted in the procedure for determining the murabaha margin at the BPRS.